Personality Characters of Educators in Surah Al-'Ala - Achyar Zein; Yusnaili Budianti; Aisyah Aisyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Islamic education is currently experiencing a decline in terms of Islamic values which causes setbacks. Educational observers analyze several reasons for the decline, including the material of life that does not refer to its main source, the occurrence of social and cultural crises, the loss of good examples, the right faith, and Islamic values. This problem requires the right solution in order to immediately get a solution so that the Islamic education process is able to run as expected. For this reason, it is necessary to refer to the Qur'an as a solution to the personality characteristics of educators. In this study, the researcher chose Surah Al-A‟la as the Surah of choice to examine the personality characteristics of the educators contained in it. This type of research is library research, which is a document study whose data sources come from written materials whose discussion is related to the character of educators. Researchers found the relevance of the character of educators to Islamic education, namely aqidah is the basic foundation that humans must have. This foundation must be firmly planted and realized in the form of habituation in order to form a character that is uswatun hasanah, namely noble character that can be imitated and followed by students and those around them. Then the relationship between educators as innovators, mentors, motivators and advisors is a form of attitude that is needed and must exist in educators so that the goals of Islamic education are successful.